The Effect of Profit Sharing Financing and Receivables towards Total Assets in Islamic Banking: Case Study in BNI Syariah - Zulfikar Hasan (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2021)
The objective of my research is to observe at the relationship between receivables, profit-sharing financing to total assets at BNI Syariah Bank from 2016-2020. Total assets in BNI Syariah frequently endure fluctuations in total assets each year, whether receivables and profit-sharing financing have a significant effect on variable Y (total assets). The method that researchers run is a quantitative method using the help of SPPS software, while the variables that influence are the dependent variable receivables and profit-sharing financing. The funding channelled by BNI Syariah is essentially the same as other Islamic banks in Indonesia. Because it still uses an agreement that has long practised in the Islamic banking system, such as the Murabaha contract for the provision of receivables, Mudharabah and Musyarakah contracts for profit sharing between customers and banks. The relationship between Receivables and Revenue Sharing Financing has a positive correlation between variables. This research can also provide some connection between Murabahah and Musharaka which are one of the main product sources of BNI Syariah bank. The originality of the research that the researcher makes is his own, it is not copied and that the researcher's research idea is new and can add new knowledge.